(3BOGH GdHOGjGJ hGdJhSW hGdfgGjGJs - (3GdTjN eMeO MLGRj GdLjRj GdNdhJj GdoeMeOis ((3eMeO Hf eUWai CHhaGTI GdefRdj s)
(3ChdgG (B:s
(3CeG HYO abO SCdfj HYV ENhGfj ef GdoeMHjf Yf BOGH GdWQjb Edi Gddg JYGdi heG jMJGL Edjg GdoeQjO s
(3BNQgG (B:s
(3agh HGddg hef Gddg hYf Gddg hEdi UGQ QMeI aj GdhLhO dNdb Gddg hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(208) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs